Foodservice manual for health care institutions - Puckett, Ruby P. (Jossey-Bass, 2013)
"The fourth edition of the book that has become a classic in the field offers a comprehensive review of the management and operation of health care food service departments. This edition includes the most current data on the successful management of daily operations and includes information on a wide variety of topics such as leadership, quality control, human resource management, communications, and financial control and management. This new edition also contains information on the practical operation of the food service department that has been greatly expanded and updated to help institutions better meet the needs of the customer and comply with the regulatory standards" -- Provided by publisher.